2011
DOI: 10.1016/j.jnutbio.2010.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Procyanidin B2 and a cocoa polyphenolic extract inhibit acrylamide-induced apoptosis in human Caco-2 cells by preventing oxidative stress and activation of JNK pathway

Abstract: Humans are exposed to dietary acrylamide (AA) during their lifetime, it is therefore necessary to investigate the mechanisms associated with AA induced toxic effects.Accumulating evidence indicates that oxidative stress may contribute to AA cytotoxicity but the link between oxidative stress and AA cytotoxicity in the gastrointestinal tract, the primary organ in contact with dietary AA, has not been described. In this study, we evaluate the alterations of the redox balance induced by AA in Caco-2 intestinal cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
78
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 126 publications
(88 citation statements)
references
References 42 publications
(49 reference statements)
8
78
1
1
Order By: Relevance
“…Studies in which acrylamide was added to the cell culture medium, the oxidant parameters increased and cell damage appeared. These fi ndings support our study (55,56,(61)(62)(63).…”
Section: Discussionsupporting
confidence: 91%
“…Studies in which acrylamide was added to the cell culture medium, the oxidant parameters increased and cell damage appeared. These fi ndings support our study (55,56,(61)(62)(63).…”
Section: Discussionsupporting
confidence: 91%
“…In line with this potential mechanism of action, it has been shown that in Caco-2 cells PB2 increases the activity of antioxidant/detoxification enzymes, ECG increases the activity of GPx and EC does not affect to any activity of the protective GSHdependent enzymes (Rodríguez-Ramiro et al, 2010. In the present study ECG evokes a substantial increase in GPx activity without altering GR and GST activities in SW480 cells.…”
Section: Discussionsupporting
confidence: 85%
“…This proliferative effect could be related to the activation of key proteins in survival/proliferation pathways, since the selective blockage of the PI-3-kinase and ERK pathways by pharmacological inhibitors suppressed PB2-induced proliferation in SW480 cells, as previously shown for EC (GranadoSerrano et al, 2007). In line with this, it has been recently demonstrated that PB2 exerted a protective role against an induced oxidative stress in Caco-2 cells (Rodríguez-Ramiro et al, 2010. In addition, cellular survival seemed to depend on the induction of the ERK pathway in…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Proanthocyanidins, which are abundant from various natural sources such as apples, 1) cranberries, 2) jujube (Ziziphus jujuba) fruits, 3) cinnamon, 4) sorghum, 5) and cocoa, 6,7) are known to have beneficial effects on health: anti-tumorial, 5,8,9) anti-inflammatory, 10,11) neuroprotective, 12) hypotensive or vasorelaxant, [13][14][15] and cardioprotective. 16) An antioxidative function is believed to be a common characteristic of proanthocyanidins which enables these chemopreventive effects.…”
mentioning
confidence: 99%